2014
DOI: 10.1542/peds.2014-0439
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Obesity in Pregnancy, Gestational Weight Gain, and Risk of Childhood Asthma

Abstract: BACKGROUND AND OBJECTIVE: Environmental or lifestyle exposures in utero may influence the development of childhood asthma. In this meta-analysis, we aimed to assess whether maternal obesity in pregnancy (MOP) or increased maternal gestational weight gain (GWG) increased the risk of asthma in offspring. METHODS: We included all observational studies published until October 2013 in PubMed, Embase, CINAHL, Scopus, The Cochrane D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
160
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(174 citation statements)
references
References 50 publications
11
160
0
3
Order By: Relevance
“…A meta-analysis of 14 studies and 108,321 mother-child pairs showed that maternal overweight or obesity in pregnancy was associated with increased risks of childhood asthma or wheeze ever (OR 1.31, 95% CI 1.16, .49) and current asthma or wheeze (1.21, 1.07, .37), independent of offspring body mass index (BMI) [38]. The studies that explored the links between maternal obesity and DNA methylation in the offspring are somewhat inconsistent in their results but point to an association between maternal BMI and neonatal DNA methylation at a limited number of CpG sites.…”
Section: Maternal Obesitymentioning
confidence: 99%
“…A meta-analysis of 14 studies and 108,321 mother-child pairs showed that maternal overweight or obesity in pregnancy was associated with increased risks of childhood asthma or wheeze ever (OR 1.31, 95% CI 1.16, .49) and current asthma or wheeze (1.21, 1.07, .37), independent of offspring body mass index (BMI) [38]. The studies that explored the links between maternal obesity and DNA methylation in the offspring are somewhat inconsistent in their results but point to an association between maternal BMI and neonatal DNA methylation at a limited number of CpG sites.…”
Section: Maternal Obesitymentioning
confidence: 99%
“…The most recent meta-analysis of 14 high-quality studies reported that children are 30-50% more likely to develop asthma or wheeze when mothers are obese at conception compared to the children of mothers with a normal body mass index (BMI; online suppl. table 1) [33]. Although maternal BMI in the obese range is clearly associated with a greater likelihood of asthma or wheeze in children, maternal overweight was not identified as a statistically significant determinant.…”
Section: Parental and Periconceptional Factorsmentioning
confidence: 99%
“…A meta-analysis among 14 European birth cohort studies showed that maternal overweight and obesity during pregnancy were associated with the risk of ever wheezing and recurrent wheezing until the age of 2 years [42] . Accordingly, a more recent meta-analysis among 14 studies with over 108,000 mother-child pairs showed that maternal obesity during pregnancy was associated a 31% increased risk of asthma or ever wheezing in children aged 14 months to 16 years [43] . Each 1-kg/m 2 increase in maternal BMI led to a 3% increased risk of childhood asthma [43] .…”
Section: Childhood Outcomesmentioning
confidence: 99%
“…Accordingly, a more recent meta-analysis among 14 studies with over 108,000 mother-child pairs showed that maternal obesity during pregnancy was associated a 31% increased risk of asthma or ever wheezing in children aged 14 months to 16 years [43] . Each 1-kg/m 2 increase in maternal BMI led to a 3% increased risk of childhood asthma [43] . High gestational weight gain was associated with a 16% higher risk of ever asthma or wheezing, but not with current asthma or wheeze [43] .…”
Section: Childhood Outcomesmentioning
confidence: 99%